On the Ethics of Real-Life Examples of Argument - Aikin, Scott F. (Informal Logic, 2024)
Argumentation theorists know that their work has real-life application, and similarly, they draw inspiration for that work from real-life experiences. Sometimes, it comes from some public medium – the newspaper, a blog, a debate stage. But we also draw from more private reason-exchanges – a conversation with a neighbor, small-talk with a colleague, or a lovers’ spat. A few worries about publicly theorizing about those more private cases arise. We may be making public something that was unguarded, and so betray a trust. Our theoretical reflections may themselves warp the relationship we’d originally savored, particularly when our partners know about the possibility of them being publicly scrutinized. Novelists and poets regularly struggle with this challenge with their work, and we argumentation theorists should, too.